Handbook of social psychology - F; Fiske, Susan T.; Gilbert, Daniel T.; Lindzey, Gardner (London John Wiley & Sons, Inc., 2010)
The classic Handbook of Social Psychology has been the standard professional reference for the field of social psychology for many years. Now available in a new edition, Volume 2 of this internationally acclaimed work brings readers up to date with new chapters on social neuroscience, mind perception, morality, and social stratification. The editors have structured Volume 2 in a way that highlights the many levels of analysis used by contemporary psychologists. All academics, graduate students, and professional social psychologists will want to own a copy of this landmark work.